1985
DOI: 10.1021/ac00280a023
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray interface for liquid chromatographs and mass spectrometers

Abstract: detector but not by the mass spectrometer. Those compounds account for the four unidentified peaks appearing between 15 and 30 min in the absorbance chromatogram (Figure 3).The utility of reconstructed mass chromatograms is evident in Figure 4. BHT and Irganox 1076 are easily detected in the reconstructed mass chromatogram, but in the total ion current chromatogram, Irganox 1076 is obscured by the peak at scan 557.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
695
0
15

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,433 publications
(714 citation statements)
references
References 28 publications
4
695
0
15
Order By: Relevance
“…1 Fenn et al further demonstrated the applications ESI in mass spectrometry (MS) techniques in the early 1980s 2,3 and received the Nobel prize in chemistry in 2002 due to this invention. ESI has become one of the most important and powerful ionization techniques for MS because of its effectiveness in detecting large biomolecules 4 and ease-ofuse for interfacing liquid-based separation techniques such as liquid chromatography (LC) 5,6 and capillary electrophoresis (CE). [7][8][9] A conventional ESI source typically employs flow rates in the range of 4-200 μL/min through a capillary that has 50-200 μm inner diameter (i.d.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Fenn et al further demonstrated the applications ESI in mass spectrometry (MS) techniques in the early 1980s 2,3 and received the Nobel prize in chemistry in 2002 due to this invention. ESI has become one of the most important and powerful ionization techniques for MS because of its effectiveness in detecting large biomolecules 4 and ease-ofuse for interfacing liquid-based separation techniques such as liquid chromatography (LC) 5,6 and capillary electrophoresis (CE). [7][8][9] A conventional ESI source typically employs flow rates in the range of 4-200 μL/min through a capillary that has 50-200 μm inner diameter (i.d.).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] A conventional ESI source typically employs flow rates in the range of 4-200 μL/min through a capillary that has 50-200 μm inner diameter (i.d.). 5 A micro-electrospray source makes use of a tapered emitter with a small terminal orifice (usually < 20 μm i.d.) and much lower flow rates in the range of 0.1-1μL/min.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ionization in LC/MS typically occurs at atmospheric pressure and the ions are swept into the vacuum system through differentially pumped regions separated by apertures or capillaries [4]. Ionization in atmospheric pressure LC/MS is by electrospray ionization (ESI) [5], corona discharge ionization [atmospheric pressure chemical ionization (APCI)] [6], photo ionization [7], or surface ionization [8]. Because ionization in GC/MS occurs under vacuum conditions and in LC/MS occurs at atmospheric pressure, the two separation methods require entirely different interfaces to the mass spectrometer and are thus usually performed on instruments dedicated to the particular chromatography method.…”
mentioning
confidence: 99%
“…In recent years, atmospheric pressure mass spectrometers have proliferated, primarily because of electrospray ionization and the ease of interfacing this atmospheric pressure ionization method to liquid chromatographs [5]. In addition, many of the mass spectrometers currently used for LC/MS have capability for MS n studies and/or accurate mass measurement, capabilities that are more rare for GC/MS instrumentation.…”
mentioning
confidence: 99%
“…This system is capable of subfemtomole nanoflow LC-MS sensitivity in both positive and negative ion mode across the solvent gradient. and electrospray ionization-mass spectrometry (ESI-MS) has evolved substantially since its initial implementation in the 1980s [1]. Traditional LC systems operated at solvent flow rates that were orders of magnitude higher (hundreds of L/min to mL/min) than those used for mass spectrometry (tens of L/ min), resulting in the need for solvent flow splitters [2].…”
mentioning
confidence: 99%